2007
DOI: 10.1111/j.1464-410x.2007.06689.x
|View full text |Cite
|
Sign up to set email alerts
|

The utility of magnetic resonance imaging and spectroscopy for predicting insignificant prostate cancer: an initial analysis

Abstract: from surgical pathology as organ-confined cancer of ≤ 0.5 cm 3 with no poorly differentiated elements. The accuracy of predicting insignificant prostate cancer was assessed using areas under receiver operating characteristic curves (AUCs), for previously reported clinical models and for newly generated MR models combining clinical variables, and biopsy data with MRI data (MRI model) and MRI/MRSI data (MRI/MRSI model). RESULTSAt pathology, 41% of patients had insignificant cancer; both MRI (AUC 0.803) and MRI/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 46 publications
7
111
1
2
Order By: Relevance
“…2). Evidence already exists that metabolite changes may occur in the tissues adjacent to prostate tumor since, for example, prostate tumors smaller than 0.5 cm 3 (defined by histopathology) have been assessed as being larger than 0.5 cm 3 when using the metabolite ratio (choline + spermine + creatine)/citrate to determine the extent of metabolic abnormality 1, 17. In the present study it was observed that citrate and spermine concentrations are both systematically decreased in the tissues immediately adjacent to prostate tumor regions, defined by morphological imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Evidence already exists that metabolite changes may occur in the tissues adjacent to prostate tumor since, for example, prostate tumors smaller than 0.5 cm 3 (defined by histopathology) have been assessed as being larger than 0.5 cm 3 when using the metabolite ratio (choline + spermine + creatine)/citrate to determine the extent of metabolic abnormality 1, 17. In the present study it was observed that citrate and spermine concentrations are both systematically decreased in the tissues immediately adjacent to prostate tumor regions, defined by morphological imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, while morphological MRI techniques such as T 2 ‐ and diffusion‐weighted (DW)‐MRI are effective at identifying large prostate tumors in the peripheral zone, they are less effective at detecting small tumors1, 2 and in differentiating central gland tumors from benign disease. Additionally, the biological aggressiveness of prostate tumors (which equates with histological Gleason grade) is indistinguishable using conventional morphological MRI techniques 3, 4.…”
mentioning
confidence: 99%
“…Researchers in numerous studies have suggested that magnetic resonance (MR) imaging, used alone or in combination with functional or metabolic MR imaging techniques, such as MR spectroscopic imaging, can contribute valuable information to the pretreatment assessment of prostate cancer (4,(11)(12)(13)(14)(15)(16)(17)(18). Therefore, the purpose of our study was to prospectively evaluate the diagnostic performance of T2-weighted MR imaging and MR spectroscopic imaging in detecting lesions stratified by pathologic volume and Gleason score in men with clinically determined low-risk prostate cancer.…”
Section: Genitourinary Imaging: Mr Performance Characteristics In Lowmentioning
confidence: 99%
“…Shukla-Dave et al (15) analyzed the capability of MR imaging and combined MR imaging and MR spectroscopic imaging to help predict clinically insignificant cancer at prostatectomy in 220 patients with low-risk prostate cancer (defined as clinical stage T1c or T2a, PSA level of ,20 ng/ mL [20 mg/L], and Gleason score of 6 at biopsy). Models incorporating clinical, biopsy, and MR data performed significantly better (AUC, 0.80-0.85) than models incorporating only clinical and biopsy data (AUC, 0.57-0.73) (15).…”
Section: Genitourinary Imaging: Mr Performance Characteristics In Lowmentioning
confidence: 99%
“…To date, there are no long-term prospective studies regarding the use of mpMRI in AS. Using a 220 patient cohort, Shukla-Dave et al 60 developed a nomogram based on clinicopathological data and mpMRI findings; this nomogram demonstrated a high area under the receiver operating characteristic curve (AUC) of 0.854 for selecting patients appropriate for AS. A follow-up study of 181 patients revealed an AUC of only 0.738 for low-risk disease (defined as ≤pT2, Gleason grade<4, and tumor volume ≤ 0.5 cc) for those who underwent radical prostatectomy.…”
Section: Multiparametric Mri In Active Surveillancementioning
confidence: 99%